2009
DOI: 10.1016/s0025-6196(11)60543-0
|View full text |Cite
|
Sign up to set email alerts
|

Proposal for a Collaborative Approach to Clinical Teaching

Abstract: Evidence suggests that inexperienced clinical teachers are often controlling and noninteractive. Adult learning theory states that mature students prefer shared and self-directed learning and that skillful teachers favor facilitating discussions over transmitting knowledge. Similarly, education research shows that effective clinical teachers invest in relationships with learners, ask questions to diagnose learners, communicate complex information clearly, and provide meaningful feedback. On the basis of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 32 publications
3
40
0
2
Order By: Relevance
“…A basic summary of the curricular content of FEED was previously published. 13 These topics are taught by experienced, award-winning teachers in 2-hour sessions involving small groups of fewer than 20 participants, and using interactive and discussion-based learning methods that are intended to role model effective clinical teaching. Each of the 2-hour sessions addresses 1 of the basic topics listed above and is offered multiple times during 1 year to allow faculty members to attend at times that are convenient for their schedules.…”
Section: Study Intervention: Faculty Development Program For Clinicalmentioning
confidence: 99%
See 2 more Smart Citations
“…A basic summary of the curricular content of FEED was previously published. 13 These topics are taught by experienced, award-winning teachers in 2-hour sessions involving small groups of fewer than 20 participants, and using interactive and discussion-based learning methods that are intended to role model effective clinical teaching. Each of the 2-hour sessions addresses 1 of the basic topics listed above and is offered multiple times during 1 year to allow faculty members to attend at times that are convenient for their schedules.…”
Section: Study Intervention: Faculty Development Program For Clinicalmentioning
confidence: 99%
“…12 The goals of remediation should model recognized qualities of excellent teachers, which would include the abilities to create a positive learning environment, engage in dialogue, provide effective feedback, diagnose learners' needs, use known teaching methods, and develop personal philosophies of teaching. 13 There is mixed evidence on the interaction between faculty's preintervention skills and the effectiveness of a faculty development program. Litzelman et al 14 found that teachers with low learner baseline ratings showed poor improvement in teaching performance after receiving feedback, compared to teachers with high baseline ratings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review of clinical teaching research found that interpersonal relationships between teachers and learners are important. 13 Successful teaching behaviors include demonstrating enthusiasm, 14 promoting dialogue, 15 and spending extra time with learners. 16 Clinical teachers should also know basic skills like asking questions, diagnosing learners, utilizing teaching frameworks, and giving meaningful feedback.…”
mentioning
confidence: 99%
“…16 Clinical teachers should also know basic skills like asking questions, diagnosing learners, utilizing teaching frameworks, and giving meaningful feedback. 15 Finally, master teachers seem to prefer facilitating discussions over transmitting knowledge, [17][18][19] and they promote learner growth by balancing challenge and support. 20 Despite the abundance of research on clinical teaching, a limitation of many previous studies has been the use of Published online August 11, 2010 heterogeneous samples of teachers.…”
mentioning
confidence: 99%